A numerical study on fetal head molding during labor. (8th November 2020) - Moura, Rita; Borges, Margarida; Vila Pouca, Maria C. P.; Oliveira, Dulce A.; Parente, Marco P. L.; Kimmich, Nina; Mascarenhas, Teresa; Natal, Renato M.
Abstract: During vaginal delivery, the fetal head molds into an elongated shape to adapt to the birth canal, a process known as fetal head molding. However, excessive molding can occur due to prolonged labor or strong contractions, leading to several disorders on the fetal head. This work aims to perform a numerical study on the biomechanics of fetal head molding by measuring specific diameters and the corresponding molding index. A finite element model of the pelvic floor muscles and the fetal body was used. The fetal head is composed of the skin and soft tissues, the skull with sutures and fontanelles, and the brain. The sutures and fontanelles were modeled with membrane elements and characterized by a visco‐hyperelastic constitutive model adapted to a plane stress state. Simulations were performed to replicate the second stage of labor in the vertex presentation and occipito‐anterior position. With the introduction of viscoelasticity to assess a time‐dependent response, a prolonged second stage of labor resulted in higher molding. The pressure exerted by the birth canal and surrounding structures, along with the presence of the pelvic floor muscles, led to a percentage of molding of 9.1%. Regarding the pelvic floor muscles, a 19.4% reduction on the reaction forces and a decrease of 2.58% in muscle stretching was reported, which indicates that sufficient molding may lead to fewer injuries. The present study demonstrates the importance of focusing on the fetus injuries with non‐invasive methods that can allow to anticipate complications during labor. Abstract : This study presents a finite element model suitable to analyze the fetal head molding during childbirth. Modeling the sutures and fontanelles of the fetal head with membrane elements represents the molding process more accurately, with an increase in the maxillo‐vertical and a decrease in the suboccipito‐bregmatic diameter. The pressure exerted by the birth canal and surrounding structures is considered. With the introduction of viscoelasticity to assess a time‐dependent response, a prolonged second stage of labor resulted in higher molding.